PREVENTIVE DENTISTRY: APPROACHES TO DISEASE PREVENTION RATHER THAN TREATMENT - Abduraxmonova, Shohista (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Preventive dentistry focuses on maintaining oral health and preventing the onset of dental diseases rather than treating them after they occur. This field emphasizes regular dental check-ups, proper oral hygiene practices, balanced nutrition, and the use of fluoride to strengthen tooth enamel. Through preventive approaches, such as dental sealants, professional cleanings, and patient education, individuals can significantly reduce the risk of cavities, gum diseases, and tooth loss. Preventive dentistry not only helps preserve natural teeth for a lifetime but also reduces healthcare costs and improves overall quality of life. The importance of prevention lies in its ability to identify early signs of dental issues and address them before they develop into more serious conditions.